2008
DOI: 10.1016/j.jri.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal IL-8 levels are positively associated with Candida albicans and inversely with lactobacilli in HIV-infected women

Abstract: IL-8/ CXCL8 is induced during infections, but has not been reported for Candida albicans colonization of the female genital tract. Cervicovaginal lavage (CVL) samples were collected from 406 HIV-infected women. IL-8 levels were evaluated by ELISA and compared with levels of C. albicans detected by potassium hydroxide (KOH) and PCR. Levels of lactobacilli, Gardnerella vaginalis and Mycoplasma hominis were also determined by PCR. IL-8 was significantly higher in samples from women with Candida, and regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…We now demonstrate for the first time using an expanded panel of innate immunity mediators that this immuno-modulatory phenomenon is also true for the L. jensenii isolate 1153 and its bioengineered derivatives. The results of our study agree with clinical observations showing an association of vaginal lactobacilli with relatively low levels of pro-inflammatory mediators in-vivo [56-58]. Furthermore, the results from our in-vitro model are in agreement with findings generated in a macaque model of SHIV infection [26].…”
Section: Discussionsupporting
confidence: 91%
“…We now demonstrate for the first time using an expanded panel of innate immunity mediators that this immuno-modulatory phenomenon is also true for the L. jensenii isolate 1153 and its bioengineered derivatives. The results of our study agree with clinical observations showing an association of vaginal lactobacilli with relatively low levels of pro-inflammatory mediators in-vivo [56-58]. Furthermore, the results from our in-vitro model are in agreement with findings generated in a macaque model of SHIV infection [26].…”
Section: Discussionsupporting
confidence: 91%
“…Across studies, BV is associated with IL-1β in both US 17, 18 and Kenyan 19 women, but few reports examined IL-1β and other infections. IL-6 appears to have little relationship with any genital infection 17, 20-22 , while increased IL-8 has been associated with trichomoniasis, 23 cervicitis, 24 and yeast 25 in many, but not all 17, 25 studies. Few of these studies enrolled African women, thus we are unable to assess whether the differences we observed in associations between US and Kenyan women are an anomaly, or reflect regional differences.…”
Section: Discussionmentioning
confidence: 96%
“…25 Several groups have shown that local, genital markers of inflammation are associated with increased HIV-1 genital shedding. 12,15 Anderson et al showed that the presence of white blood cells in CVL is associated with increased detection of HIV-1 in CVL, even after controlling for plasma viral load, 26 but did not control for the presence of genital coinfections. Higher rates of genital shedding of HIV-1 are seen in women with concomitant genital tract infections such as herpes 27 or BV.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines such as interleukin (IL)-1b, tumor necrosis factor (TNF)-a, IL-6, and IL-8 are increased in many genital infections [10][11][12][13] and with genital shedding of HIV-1. [14][15][16] Vaginal hygiene practices 17 and cryotherapy for cervical neoplasia 18 have also been associated with genital HIV-1 shedding, which many hypothesize is related to inflammation resulting from trauma to vaginal epithelium.…”
Section: Introductionmentioning
confidence: 99%